Communication, Culture and Ecology Rethinking Sustainable Development in Asia (Communication, Culture and Change in Asia, 2018)
This book offers comprehensive insights into the cultural and ecological values that influence sustainable development across Asia, addressing the cultural, religious and philosophical moorings of development through participatory and grassroots communication approaches. It presents a range of contributions and case studies from leading experts in Asia to highlight the debates on environmental communication and sustainable development that are relevant today, and to provide an overview of the positive traditions of ecological sensitivity and cultural communication that may find common ground between communities. This well-researched guide to the dynamic and complex terrain of communication for sustainable development offers uniquely practical perspectives on communication, environment and sustainable development that are of immense value for policy makers, media scholars, development practitioners, researchers and students of communication and media studies.